Biochemical changes in cluster analysis indicators as a result of special tests of freestyle wrestlers of alactate and lactate types of power supply - Sybil, M.; Pervachuk, R.; Zahura, F.; Shandrygos, V.; Yaremenko, I.; Bodnar, I. (Journal of Physical Education and Sport, 2018)
The paper presents a pattern of alactic, lactic and mixed types of freestyle wrestlers identified using the cluster analysis (computer application SPSS Statistic 17) of biochemical parameters growth of alactic (creatinine) and lactic (lactic acid) anaerobic energy supply mechanisms in response to specific check tests. The study involved 20 freestyle wrestlers with classification from I degree to Master of Sports (3-8 years of experience in training). It has been established that 3 athletes belong to alactic, 6 to lactic and 11 athletes to mixed types, which made it possible to customize the training program.